2009
DOI: 10.1007/s00213-009-1520-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age on the hypnotic effects of eszopiclone and zolpidem in the guinea pig

Abstract: Rational Eszopiclone and zolpidem are hypnotics that differentially affect sleep and waking states in adult animals. Therefore, it was of interest to compare their effects on the states of sleep and wakefulness in aged animals. Objectives Our objective was to determine the responses to eszopiclone and zolpidem vis-à-vis sleep and waking states in aged guinea pigs and to compare them with the effects of these hypnotics in adult animals. Methods Aged guinea pigs were prepared to monitor sleep and waking states a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…For example, in adult rats, intraperitoneal administration of zopiclone in doses ranging from 2.5 to 10 mg/kg was found to decrease W, decrease latency of SWS, increase total amount of time spent in SWS, increase the latency of REM sleep, and decrease the total amount of time spent in REM sleep [34, 35, 95]. Similarly in the guinea pigs, intraperitoneal administration of 1, 3, and 10 mg/kg doses of eszopiclone were shown to decrease W and the latency of SWS and to increase the total amount of time spent in SWS [110, 111]. These two studies reported that the administration of eszopiclone increases the latency of REM sleep but did not reduce the total amount of time spent in REM sleep over a period of 2 h. Like these animal studies, Zopiclone has been shown in humans to shorten sleep latency and increase total sleep [40, 87].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, in adult rats, intraperitoneal administration of zopiclone in doses ranging from 2.5 to 10 mg/kg was found to decrease W, decrease latency of SWS, increase total amount of time spent in SWS, increase the latency of REM sleep, and decrease the total amount of time spent in REM sleep [34, 35, 95]. Similarly in the guinea pigs, intraperitoneal administration of 1, 3, and 10 mg/kg doses of eszopiclone were shown to decrease W and the latency of SWS and to increase the total amount of time spent in SWS [110, 111]. These two studies reported that the administration of eszopiclone increases the latency of REM sleep but did not reduce the total amount of time spent in REM sleep over a period of 2 h. Like these animal studies, Zopiclone has been shown in humans to shorten sleep latency and increase total sleep [40, 87].…”
Section: Discussionmentioning
confidence: 99%
“…The same study further reported that the administration of zolpidem at 7.5 mg/kg dose increased latency and decreased amount of time spent in REM sleep. However, in adult guinea pigs intraperitoneal administration of zolpidem at 3 and 10 mg/kg doses was found to decrease the amount of time spent in W and increase the amount of time spent in SWS but not the REM sleep [110, 111]. Like these animal studies, studies in human subjects have shown that zolpidem, in doses between 5 and 20 mg, shortens the latency to non-REM sleep and also increases the total amount of non-REM sleep [1, 88, 107].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations